Towards smarter harvesting from natural palm populations by sparing the individuals that contribute most to population growth or productivity. Issue 4 (13th February 2018) - Jansen, Merel; Anten, Niels P. R.; Bongers, Frans; Martínez‐Ramos, Miguel; Zuidema, Pieter A.
Abstract: Natural populations deliver a wide range of products that provide income for millions of people and need to be exploited sustainably. Large heterogeneity in individual performance within these exploited populations has the potential to improve population recovery after exploitation and thus help sustain yields over time. We explored the potential of using individual heterogeneity to design smarter harvest schemes, by sparing individuals that contribute most to future productivity and population growth, using the understorey palm Chamaedorea elegans as a model system. Leaves of this palm are an important non‐timber forest product and long‐term inter‐individual growth variability can be evaluated from internode lengths. We studied a population of 830 individuals, half of which was subjected to a 67% defoliation treatment for 3 years. We measured effects of defoliation on vital rates and leaf size—a trait that determines marketability. We constructed integral projection models in which vital rates depended on stem length, past growth rate and defoliation and evaluated transient population dynamics to quantify population development and leaf yield. We then simulated scenarios in which we spared individuals that were either most important for population growth or had leaves smaller than marketable size. Individuals varying in size or past growth rate responded similar to leaf harvesting in terms of growth and reproduction. By contrast, a reduction in survival chance was smaller in large individuals than in small ones. Simulations showed that harvest‐induced population decline was greatly reduced when sparing individuals from size and past growth classes that contributed most to population growth. Under this scenario, cumulative leaf harvest over 20 years was somewhat reduced, but long‐term leaf production was sustained. A threefold increase in leaf yield was generated when individuals with small leaves were spared. Synthesis and applications . This study demonstrates the potential to create smarter systems of palm leaf harvest by accounting for individual heterogeneity within exploited populations. Sparing individuals that contribute most to population growth ensured sustained leaf production over time. The concepts and methods presented here are generally applicable to exploited plant and animal species which exhibit considerable individual heterogeneity. Abstract : This study demonstrates the potential to create smarter systems of palm leaf harvest by accounting for individual heterogeneity within exploited populations. Sparing individuals that contribute most to population growth ensured sustained leaf production over time. The concepts and methods presented here are generally applicable to exploited plant and animal species which exhibit considerable individual heterogeneity.